Relativistic Hartree-Bogoliubov description of deformed light nuclei - Lalazissis, G. A.; Vretenar, D.; Ring, P. (HNPS Advances in Nuclear Physics, 2020)
The Relativistic Hartree-Bogoliubov model is applied in the analysis of ground- state properties of light nuclei with 4 < Ζ < 11. The model uses the NL3 effective interaction in the mean-field Lagrangian, and describes pairing correlations by the pairing part of the finite range Gogny interaction DIS. Neutron separation energies, quadrupole deformations, nuclear matter radii, and differences in radii of proton and neutron distributions are compared with recent experimental data.